Efektivitas Penggunaan Face Id Pada Pelayanan Pendaftaran Pasien Bpjs Rawat Jalan di Rs Tni Dustira - Pertiwi Kartika Putri; Yuyun Yunengsih (Jurnal Infokes, 2026)
This study aims to determine the effectiveness of using Face ID technology in the registration process for BPJS outpatient services at Dustira Military Hospital. The implementation of this technology is intended to speed up the registration process while improving the accuracy of patient identity verification. However, various issues have been encountered during implementation, such as facial recognition failures in elderly patients, technical issues like inadequate lighting, and inconsistent understanding of procedures among patients. The research method employed is a qualitative descriptive approach, with data collection techniques including direct observation, in-depth interviews with registration staff and BPJS outpatient patients, and a review of relevant literature. The research results indicate that the average registration time using Face ID only takes 1–3 minutes, which is faster than the manual method. However, technical challenges and human resource readiness remain the primary obstacles to its implementation. Therefore, regular system evaluations, improvements in lighting quality, provision of alternative identification methods, technical training for staff, and comprehensive patient education are necessary to ensure that the Face ID system can truly support fast, safe, and inclusive healthcare services.